Paradigma Baru Madrasah dalam Implementasi Kebijakan Kurikulum 2013 - Prastowo, Andi (Jurnal Pendidikan Islam, 2014)
Policy implementation is a process applying of decision of policy which usually early with compilation of program, project of till to activities for resolving a problem of becoming policy agenda. Ministry of Religion Republic Of Indonesia also have plan for the implementation of policy of Curriculum 2013 in all ladder of madrasah, including one of them at ladder of madrasah ibtidaiyah, start year 2014. This implementation have of implication to change various education aspect in madrasah like Standard Process, Standard Content, Standard Interest Grad, Standard Assessment, and also at Textbook Iesson. This paradigm becomes someone reference or institution in taking decision and policy to act.